Peningkatan Hasil Pendidikan Nilai - Nilai Kehidupan Sosial melalui Penerapan Pembelajaran Kooperatif - Isminiati, Ch (Fakultas Ilmu Pendidikan UNY, 2008)
Being able to contribute in constructive way to activities of social and democratic society is an essential skill in school and in life. Most of what the child will do in life will be in cooperation with other people. A consequently, the social skills and social living values in education are very important to learn. Therefore, teacher needs to choose an appropriate .instructional strategies to teach the skills andliving values, i.e.: cooperation, caring, responsibility, honesty, respect, simplicity, tolerance, unity, open-mindedness, love, happiness, freedom, empathy, humility. Cooperative learning is one of the appropriate strategies to teach those skills and values. When it is applied properly, many living values will be studied by students, those are: cooperation, responsibility, tolerance, unity, respect, caring, love. Key Words: social and democratic society, Social skills, living values, cooperative learning